Altruism or the Other as the Essence of Existence : A Philosophical Passage to Being Altruistic - Ioannidis, Iraklis, (Value Inquiry Book Series ;, 2021)
"The author offers fresh, yet radical, philosophical insights into the much contested topic of altruism. Whereas the debate on altruism, since time immemorial, consists in trying to determine whether we are biologically altruistic or not, Ioannidis explores altruism otherwise. Following Nietzsche, he traces altruism to the phenomenon of promising or giving one's word. His analysis provokes us to think that our possibility to exist cannot be realized without this event"--